(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Mission command as a phenomenon, mission command philosophy and challenges of the Early 21-st Century. This paper presents the results of the authors' research related to mission command and its role in planning and conducting operations in the early 21st century.